2018
DOI: 10.3389/fevo.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae Alter Toxin Sequestration and Performance of Two Specialist Herbivores

Abstract: Multitrophic species interactions are shaped by both top-down and bottom-up factors. Belowground symbionts of plants, such as arbuscular mycorrhizal fungi (AMF), can alter the strength of these forces by altering plant phenotype. For example, AMF-mediated changes in foliar toxin and nutrient concentrations may influence herbivore growth and fecundity. In addition, many specialist herbivores sequester toxins from their host plants to resist natural enemies, and the extent of sequestration varies with host plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 134 publications
(229 reference statements)
0
22
0
Order By: Relevance
“…The commercial AMF mix was purported to consist of four AMF species, and AMF species vary in nutrient trading and resulting effects on plant phenotype , Thonar et al 2014, Argüello et al 2016). However, we consider this explanation to be unlikely; cloning and Sanger sequencing of the AMF mix, and of milkweed roots from plants grown under the same experimental conditions, revealed that the AMF mix consisted only of Funneliformis mosseae (Meier and Hunter 2018a). Therefore, the differential effects of medium and high AMF inoculum availability on herbivore-induction of defenses are more likely due to plant suppression of AMF colonization under high AMF inoculum availability than to differential colonization by AMF species.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The commercial AMF mix was purported to consist of four AMF species, and AMF species vary in nutrient trading and resulting effects on plant phenotype , Thonar et al 2014, Argüello et al 2016). However, we consider this explanation to be unlikely; cloning and Sanger sequencing of the AMF mix, and of milkweed roots from plants grown under the same experimental conditions, revealed that the AMF mix consisted only of Funneliformis mosseae (Meier and Hunter 2018a). Therefore, the differential effects of medium and high AMF inoculum availability on herbivore-induction of defenses are more likely due to plant suppression of AMF colonization under high AMF inoculum availability than to differential colonization by AMF species.…”
Section: Discussionmentioning
confidence: 92%
“…We describe key results in more detail below. Note that we have reported the effects of AMF on the traits of the undamaged (control) milkweeds previously in a manuscript on herbivore performance (Meier and Hunter 2018a). Here, we use data from the control plants only to measure the magnitude of induction in treatment (herbivore-damaged) plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent of our knowledge, this is the first report studying the outcome of insect–plant–microbe interactions with a focus on phloem feeders’ probing and feeding behavior on a leguminous plant with different levels of root colonization by AM fungi. In general, positive effects of the AM symbiosis on phloem feeders have been documented (Gange et al ., ; Hempel et al ., ; Koricheva et al ., ; Babikova et al ., ; Simon et al ., ; Maurya et al ., ; Meier & Hunter, ). In previous studies, the extent of root colonization by AM fungi ranged between 15% and 55% RLC.…”
Section: Discussionmentioning
confidence: 97%
“…The indirect effects of AM fungi on plant interactions with aphids has resulted in beneficial (Gange et al, 2002;Babikova et al, 2014a;Maurya et al, 2018;Meier & Hunter, 2018), detrimental (Guerrieri et al, 2004;Babikova et al, 2013;Maurya et al, 2018;Meier & Hunter, 2018), or no effects on aphids (Gehring & Bennett, 2009;Hartley & Gange, 2009;Karley et al, 2017). Previous research found a positive effect of the AM symbiosis on aphid adult weight (Gange & West, 1994;Gange et al, 1999), percent growth (Gange et al, 2002), and aphid abundance (Babikova et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%